No monkey business: why studying NK cells in non-human primates pays off - Hong, Henoch S.; Rajakumar, Premeela; Billingsley, James M.; Reeves, R. Keith; Johnson, R P. (Frontiers in Immunology, 2013)
Human NK cells play a key role in mediating host immune responses against various infectious diseases. For practical reasons, the majority of the data on human NK cells has been generated using peripheral blood lymphocytes. In contrast, our knowledge of NK cells in human tissues is limited, and not much is known about developmental pathways of human NK cell subpopulations in vivo. Although research in mice has elucidated a number of fundamental features of NK cell biology, mouse and human NK cells significantly differ in their subpopulations, functions and receptor repertoires. Thus, there is a need for a model that is more closely related to humans and yet allows experimental manipulations. Nonhuman primate models offer numerous opportunities for the study of NK cells, including the study of the role of NK cells after solid organ and stem cell transplantation, as well as in acute viral infection. Macaque NK cells can be depleted in vivo or adoptively transferred in an autologous system. All of these studies are either difficult or unethical to carry out in humans. Here we highlight recent advances in rhesus NK cell research and their parallels in humans. Using high-throughput transcriptional profiling, we demonstrate that the human CD56bright and CD56dim NK cell subsets have phenotypically and functionally analogous counterparts in rhesus macaques. Thus, the use of nonhuman primate models offers the potential to substantially advance human NK cell research.